Psychological impact of autologous hematopoietic stem cell transplantation in systemic sclerosis patients and influence of resilience - Schmalzing, Marc; Gernert, Michael; Fröhlich, Matthias; Henes, Jörg; Schwindl, Nathalie; Zerhusen, Leona; Berthold, Lukas; Hewig, Johannes; Kübler, Andrea; Pecher, Ann-Christin; Kleih-Dahms, Sonja; Strunz, Patrick-Pascal; et al. (Frontiers in Immunology, 2024)
Objective: In severe cases of systemic sclerosis (SSc), autologous hematopoietic stem cell transplantation (aHSCT) is superior compared to cyclophosphamide. But treatment related morbidity and mortality have to be considered. To date, data on major physical and psychological impacts of aHSCT are scarce. Therefore, subjectively experienced physical and psychological impact of aHSCT and exploration of internal and external factors helping to cope with aHSCT was assessed.Methods: Retrospective assessment of physical and psychological variables in an SSc cohort after aHSCT to describe: Health-related quality of life (HRQL), SSc-associated impairment, coping strategies, body image, and resilience. Additionally, semi-structured interviews were conducted and analysed via mixed methods qualitative content analysis.Results: Thirty-two patients were included. HRQL correlated with impairment due to SSc and with depressive coping. An unfavourable body image correlated with reduced HRQL and increased impairment but improves after aHSCT. Patients with good resilience had a better HRQL, less depressive coping, and less SSc-associated impairment. The semi-structured interviews revealed that resilience is important for a successful disease management as patients with higher resilience were more satisfied with aHSCT, patients with lower resilience would have wished for more psychological support. Thirty-one patients would recommend aHSCT to other patients.A transient negative impact of aHSCT on mental well-being is present but can be relieved by a team specialised to aHSCT. Psychological support seems to be an unmet need, particularly in patients with low resilience. Patients with higher resilience described a lower negative impact caused by aHSCT and higher satisfaction after therapy.